Flash Card Media Development to Reduce Identity Crises in High School Students - Haliza, Alvi Nur; Cahyaningrum, Vesti Dwi; Efendi, Moh. Yusuf (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2026)
Adolescence is a crucial phase in identity formation; however, it is often accompanied by identity crises that trigger anxiety, low learning motivation, and difficulties in social relationships. This study aims to develop flash cards as a valid and practical tool to support Guidance and Counseling services, with the goal of enhancing self-exploration and fostering identity commitment among high school students. The method used was Research and Development (R&D) based on the Borg and Gall model, limited to the seventh stage (Product Revision II). The data collection instruments included interviews, a student needs questionnaire, and a media acceptability questionnaire for validation testing. The data were analyzed using the Percentage of Agreement technique. The results showed that the developed flash card media achieved an average validation score of 94.67%, categorized as “Highly Suitable.” Specifically, the assessment results from subject matter experts reached 95.61%, media experts 95.55%, and prospective users 92.85%. These flash cards meet the qualifications for implementation in schools as an interactive innovation in Guidance and Counseling services to help students overcome identity crises in accordance with their psychosocial developmental stages.